Modeling Crystallization of Basalt Magmas Along the Reykjanes Ridge - Schultz, Rachel M. (The Ohio State University, 2017)
The Reykjanes Ridge is a section of the Mid-Atlantic ridge located south of Iceland and extending to the south west from the Reykjanes Peninsula. This ridge is interesting because it intersects a mantle plume centered beneath Iceland and therefore provides the opportunity to study how magma plumbing systems are affected by the additional heat provided by a mantle plume. Geophysical, geochemical and petrological studies show that along the ridge towards Iceland the oceanic crust thickens and that pre-eruptive magmatic water contents increase. To understand magma crystallization and crustal accretion along the Reykjanes Ridge, parent melt compositions were selected from glasses sampled from different segments of the ridge. The melt compositions generated by crystallization of these parents were calculated at different pressures and magma water contents using the program Petrolog3. The calculated melt compositions were compared with the natural compositions of glasses collected from the different ridge segments. In the southern section of the Reykjanes, liquids generated by crystallization at low pressures, about 100 MPa, and low water contents generally fit the compositional variations shown by natural samples. These results are consistent with those found for other parts of the global ridge system. However, the compositions of glasses from the northern part of the ridge are not consistent with an origin solely by crystallization at low pressures and low water contents. Compositional variations for these samples is best explained by crystallization of one parent composition at different pressures and water contents, suggesting the presence of complex plumbing systems. These results indicate that the vertical extent of magma plumbing systems correlates with crustal thickness, and that accretion of oceanic crust occurs over a range of depths. A three-year embargo was granted for this item.